Dampak Social Media Recruiting dan Online Employer Reviews Terhadap Keputusan Melamar Kerja di Bank Sumsel Babel Tanjung Raja - Muhammad Tegar Rahmatullah; Sabeli Aliya (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
The advancement of digital technology has brought significant changes to corporate recruitment strategies, including the utilization of social media recruiting and online employer reviews as tools to attract potential candidates. This phenomenon has influenced the way job seekers, particularly younger generations, make decisions about applying for jobs. This study aims to examine the impact of social media recruiting and online employer reviews on job application decisions at Bank Sumsel Babel Tanjung Raja. A quantitative approach with an associative-causal design was employed. The study involved a population of 65 respondents, all of whom were included using a total sampling technique. Data were collected through a Likert-scale questionnaire. The data analysis included tests of validity and reliability, classical assumption tests (normality, multicollinearity, and heteroscedasticity), multiple linear regression analysis, t-tests, F-test, and the coefficient of determination (R²). The results indicate that social media recruiting has a positive impact on job application decisions, with a t-value of 4.995 (p = 0.000), while online employer reviews also demonstrate a positive impact with a t-value of 4.182 (p = 0.000). Simultaneously, both variables exert a significant effect on job application decisions, as evidenced by an F-value of 57.259 (p = 0.000). These findings highlight that the strategic optimization of social media recruiting, and the management of online employer reviews can have a substantial impact on individuals’ decisions to apply for a job.